Chlorine partial pressure measurements over CuCl2/CuCl by transpiration method with gas detector tubes. (May 2023) - Ueyama, Shinji; Hatada, Naoyuki; Uda, Tetsuya
Highlights: Equilibrium Cl2 partial pressure over CuCl/CuCl2 in Ar was measured at 526–604 K. Low O2 partial pressure in Ar stabilized CuCl and realized the desired reaction. Δ H ° of the reaction was successfully determined by the third-law method. Accuracy of thermodynamic data of Cu-Cl compounds in the literature is discussed. Abstract: Copper-chlorine compounds often play important roles in many industrial processes, but no reliable values of their thermodynamic quantities have been established. In this work, we measured the equilibrium chlorine partial pressure over CuCl( s ) and CuCl2 ( s ) by the transpiration method to find accurate thermodynamic quantities of the copper-chlorine compounds. The temperature dependence of the equilibrium chlorine partial pressure is given by the following equation: log p Cl 2 / b a r = 9.805 ± 2.535 - 8633.1 ± 1433.4 T / K - 1 (from 526 to 604 K), and the standard enthalpy change of the reaction (2 CuCl2 ( s ) ⇌ 2 CuCl( s ) + Cl2 ( g )) at 298.15 K is calculated as (161.7 ± 0.48) kJ mol −1 by the third-law method. This equation and value agree well with a thermodynamic data compilation Thermodynamic Properties of Individual Substances (L.V. Gurvich, I.V. Veyts, and C.B. Alcock, vol. 1, 1989 and V. S. Iorish et al., vol. 5, http://www.chem.msu.su/rus/tsiv/, accessed 18 September 2020).